Conjugates of phosphorylated zalcitabine and lamivudine with SiO2 nanoparticles: Synthesis by CuAAC click chemistry and preliminary assessment of anti-HIV and antiproliferative activity. Issue 5 (1st March 2017) - Vasilyeva, Svetlana V.; Shtil, Alexander A.; Petrova, Albina S.; Balakhnin, Sergei M.; Achigecheva, Polina Y.; Stetsenko, Dmitry A.; Silnikov, Vladimir N.
Graphical abstract: Abstract: Conjugates of phosphorylated dideoxynucleoside antiviral drugs dideoxycytidine (zalcitabine) and lamivudine with SiO2 nanoparticles were obtained via the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click chemistry between a nucleoside triphosphate containing an alkynyl group at the γ-phosphate or azidothymidine triphosphate and SiO2 nanoparticles containing alkyl azide or alkynyl groups, respectively. 4-(Prop-2-yn-1-yloxy)butylamino group has been attached to the γ-phosphate group of dideoxycytidine (zalcitabine) and lamivudine 5′-triphosphates via the phosphoramidate linkage. New compounds were shown to be potent killers of human colon carcinoma cells. Anti-HIV activity of the conjugates was demonstrated as well. The conjugates of phosphorylated lamivudine and dideoxycytidine (zalcitabine) showed higher potency than the parent nucleosides. The conjugate of phosphorylated azidothymidine was less active against HIV-1 than the parent nucleoside probably because of the replacement of its 3′-azido group by 1, 2, 3-triazole ring. These results show an opportunity for using SiO2 nanoparticles as a transport for delivering phosphorylated nucleosides to cells in order to increase their efficiency as antiviral and anticancer drugs.